Pemetaan penelitian seputar hedging/lindung nilai pada lembaga keuangan syariah: Studi literature review - Radliyah, Diana Rahmah (Maliki Interdisciplinary Journal, 2023)
Hedging has a primary contribution in promoting conventional and sharia-based economic growth in Indonesia. The fundamental alibi regarding the meaning of Hedging, as follows: (1) Hedging is a medium intended to reduce the effect of the impact of price movements; (2) Providing conditions in doing a business that can sustain product protection and welcome the needs of producers, managers, and factories; (3) Sharing opportunities for banks to prepare larger funds to be more convincing (Mursalin, 2011). Hedging can also be defined as a strategy used to reduce the risk of business or business that is not calculated, in addition Hedging is also set to obtain a profit from investment (Arifin, 2008). This research intends to identify the development of research on Hedging in Islamic Financial Institutions (LKS) by using two methods, namely quantitative methods and literature review. The data obtained to conduct research is obtained from national journals indexed by Google Scholar and Sinta through the Perish/Harzing application. The way to collect data is first to do mapping using a qualitative method called a literature review study. Second, the results of the research obtained are 2 main topics. The results of this study can be a reference for previous researchers to conduct in-depth research.